Student Interest of the Faculty of Agriculture, Musi Rawas University For Entrepreneurship in Agriculture - Andrei; Randa Wiranata; Firdinan Wahyudi (Jurnal Ilmu Pertanian Kelingi, 2021)
This study aims to determine the interest of students of the Faculty of Agriculture, Musi Rawas University in entrepreneurship in agriculture. This research was conducted at the Faculty of Agriculture, Musi Rawas University from October 2020 to January 2021. The research method used in this research was a descriptive survey method for students of the Faculty of Agriculture, Musi Rawas University. The sampling method uses stratified random sampling, namely by paying attention to a level (strata) in the population elements. In stratified random sampling, population elements are grouped at certain levels with the aim of sampling to be evenly distributed throughout the study program and the sample representing the character of all heterogeneous population elements. The data generated from this study will be analyzed using descriptive analysis methods and interval scales. The results showed that the level of student interest in entrepreneurship seen from the average value of the research results indicator was 32, which means that the interest of students of the Faculty of Agriculture, Musi Rawas University in entrepreneurship in agriculture was in the interesting category.